SISTEM BERBASIS PENGETAHUAN UNTUK KESEHATAN DAN PERAWATAN BAYI - Sukarsa, I Made; Suwija Putra, I Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2012)
Babies are very susceptible to germs of disease, environmental factors and lack of sensitivity to the symptoms of a disease, of course is a distinct fear for parents. Therefore made a convenience by utilizing technology in the form of knowledge-based system that uses a webbased media. Knowledge-based system for health and infant care is a web-based system that presents solutions to overcome the disease in infant health problems and also provide treatment for any disease problems encountered. This system provides the facility to help users diagnose the disease in identifying health problems being faced by the baby. This identification process is done through question and answer interaction between the system with the user or user-input and the lawyer's disease symptoms. The system also provides facilities for managing knowledge is performed by the system administrators who called the Knowledge Engineer in making changes to data in the knowledge base. With this facility, the addition of knowledge, change the rules in the knowledge base and system development through the acquisition of new knowledge can be directly done without having to dismantle the system that is so. This will allow the system to keep up to date. Methods of tracing disease conclusion which is used on this system is tracking trace forward (forward chaining). Rules in the knowledge base is modeled as a tree by using the MySQL database and PHP programming language. The results of this knowledge-based inference system is diagnoses the illness of the baby. Of the system implemented, the conclusion that in general the system can run well. Nevertheless there is still a lack of success of early diagnosis of disease and very dependent on administrator with expertise in building a knowledge base.
Keywords: basis pengetahuan, bayi, penyakit bayi, perawatan bayi, web.